Гра "життя" з нерегулярним простором з межами: випадок глайдерів - Brajon, Jordan; Makarenko, Alexander (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The purpose of this article is to present the work done on the implementation of rules for gliders in a game of life with a non-regular network with boundaries. First of all, we will recall the basic principle of the game of life by mentioning some structures that appear regularly and are very important as gliders. We will improve the accuracy of the collision rules between gliders. Then, we will introduce non-regular space by adding a new state for cells in boundaries. Thus it will be necessary to give the rules relating to this new cellular automaton. We will finally deal with logic gates by giving which we obtained this modified game of life.